From Tradition To Legislation: Examining India’s Stance On Public Affection In Section 294 IPC - Kumar Pandey, Shivam (International Journal of Psychosocial Rehabilitation, 2020)
Welcome to an intriguing investigation into India’s cultural and legal landscape concerning public displays of affection. The distinction between individual expression and communal acceptance can be unclear in a country that values and treasures its traditions. This piece delves into the intricacies of Section 294 IPC of the Indian Penal Code, which governs public acts of obscenity and strives to bring awareness to the evolving attitudes towards public affection in the Indian context. We embark on a journey that takes us from ancient customs to modern-day legislation, unravelling the complexities and contradictions along the way. Join us as we scrutinize the cultural, social, and legal factors that shape India’s stance on public affection, and challenge our preconceived notions about love, intimacy, and the boundaries of public space. Brace yourself for an engrossing exploration of a subject at the intersection of culture, law, and personal liberty.